THE GENESIS OF JAKARTA AS A "BAY CITY" IN THE QUATERNARY PERIOD AND ITS IMPLICATIONS - Moehammad Ali Jambak; Yves Belgiaswara Susilo; Suherman Dwi Nuryana; Himmes Putra Yuda; Muhammad Adimas Amri; Naiy Salsabila Setiawan; Deska Sulyana; Arini Dian Lestari (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Jakarta, the capital of Indonesia, is a coastal city shaped by geological and environmental processes over the past two million years of the Quaternary Period. The Jakarta Plain was formed by a mix of land sediments from the Cisadane and Citarum Rivers and marine sediments from the Java Sea. The southern region is a volcanic highland, while the city lies on lowlands with elevations ranging from 0 to 40 meters above sea level. Aims: to investigate the geological origin and sedimentary structure of the Jakarta Plain as a bay city situated between two major river deltas and to understand the implications of its geological development for spatial planning, environmental management, groundwater utilization, land subsidence, flood control, and coastal resource management, especially in the Jakarta Bay area, which features coral reef island ecosystems. Methodology and results: the research was conducted through field observations of geological outcrops and coral reef islands in Jakarta Bay, complemented by secondary data sources. The results indicate that the plain is filled by alternating layers of terrestrial and marine sediments, with strong geological connections to the surrounding Bodetabek region (Bogor, Depok, Tangerang, Bekasi). Conclusion, significance, and impact study: The study concludes that a thorough understanding of Jakarta’s sedimentary history is essential for mitigating geological risks and supporting sustainable urban development. Furthermore, Jakarta Bay’s coral reef islands hold considerable potential for tourism, underscoring the importance of integrated coastal and environmental planning based on sound geological insight.